Kekerasan komunal : anatomi dan resolusi konflik di Indonesia - Rozi, Syafuan; Pusat Penelitian Politik (Indonesia) (Jakarta : Pustaka Pelajar, 2006)
Analysis of conlicts and their resolutions in several regions in Indonesia after the fall of the New Order
Bibliografi : p. 377-382
Keywords: Violence -- Indonesia; Violence -- Political aspects -- Indonesia; Conflict management x Indonesia; Social conflict -- Indonesia